Influence of Radiographic Soft Tissue Findings on Clinical Entrapment in Patients With Orbital Fractures. Issue 4 (June 2021) - Pontell, Matthew E.; Jackson, Kianna; Golinko, Michael; Drolet, Brian C.
Abstract : Introduction: Radiographic assessment of facial fractures with computed tomography (CT) scanning has become standard of care. As imaging resolution has improved, findings such as herniation of extraocular muscles (EOM) have become a means of diagnosing conditions like orbital entrapment. However, the sensitivity and specificity of these findings has not been well-studied. We sought to evaluate the value of radiographic findings such as fat herniation, EOM contour irregularity, and EOM herniation in predicting orbital entrapment after orbital fracture. Secondary endpoints include diplopia, abnormal EOM motility, and the need for surgical fixation. Methods: A single institution, retrospective review at a regional level 1 trauma center was conducted. Patients with orbital fractures were identified by International Classification of Disease (ICD) codes and CT reports were queried for the terms "herniation, " "herniated, " "entrapped, " and "entrapment." Four hundred records were analyzed. Results: Sixty-seven percent of radiology reports mentioned "entrapped" or "entrapment, " while the incidence of clinical entrapment was 2.8%. The odds of entrapment, diplopia, and abnormal EOM motility were higher in those with EOM herniation; however, EOM herniation had a positive predictive value of 7.9% for clinical entrapment. Fat herniation alone and EOM contour irregularity had positive predictive values of 4.2% and 4.8%, respectively. Conclusions: While the odds of entrapment appear higher in patients with EOM herniation, this imaging finding is not predictive of clinical entrapment. Fat herniation and EOM contour irregularity did not have higher odds of entrapment, nor were they predictive. Diagnosis of orbital entrapment should be based primarily on physical exam, with CT as an adjunct only. The assumption that radiographic findings indicate orbital emergencies may result in unnecessary interfacility transfers, subspecialist consultations, and emergency operative procedures. Abstract : Supplemental Digital Content is available in the text